I DiG STEM: A Teacher Professional Development on Equitable Digital Game-Based Learning - Anthony Muro Villa; Quentin C. Sedlacek; Holly Yvonne Pope (MDPI AG, 2023)
Digital game-based learning (DGBL) has the potential to promote equity in K-12 STEM education. However, few teachers have expertise in DBGL, and few professional development models exist to support teachers in both acquiring this expertise and advancing equity. To support the development of such models, we conducted a professional development to explore teacher acquisition of technological, pedagogical, and content knowledge for games (TPACK-G) during a DGBL workshop series informed by culturally relevant pedagogy. This mixed methods pilot study used pre- and post-surveys and interviews to investigate shifts in teachers' (n = 9) TPACK-G, perceptions of DGBL, and operationalizations of equity and cultural relevance. The survey findings showed increases in teachers' TPACK-G, and corroboration between the surveys and interviews showed teachers' expanded ideas about the range of applications of digital games in STEM education. However, the interviews revealed that teachers' conceptualizations of equity and cultural relevance varied considerably.